2009
DOI: 10.1021/pr800894p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phosphorylation-Dependent Binding Partners of Aquaporin-2 Using Protein Mass Spectrometry

Abstract: Vasopressin-mediated control of water permeability in the renal collecting duct occurs in part through regulation of the distribution of aquaporin-2 (AQP2) between the apical plasma membrane and intracellular membrane compartments. Phosphorylation of Ser-256 at AQP2's cytoplasmic COOHterminus is well-accepted as a critical step for translocation. The aim of this study was to identify binding partners to phosphorylated versus nonphosphorylated forms of the AQP2 COOH-terminus via a targeted comparative proteomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 58 publications
4
41
1
Order By: Relevance
“…Selectively inhibiting PP2A or PP2B using endothall, fostriecin, cantharidic acid or deltamethrin did not result in significant changes in pS269 levels, suggesting that PP1 is the most likely protein phosphatase targeting pS269-AQP2 in vivo. Our results are in line with other studies that suggest a role for PP1 in regulation of AQP2 phosphorylation (Moeller et al, 2010;Zwang et al, 2009). A functional role for protein phosphatases in regulation of AQP2 has previously been suggested, although the effects of okadaic acid observed were attributed to a depolymerizing effect (disruption) on the actin cytoskeleton (Valenti et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…Selectively inhibiting PP2A or PP2B using endothall, fostriecin, cantharidic acid or deltamethrin did not result in significant changes in pS269 levels, suggesting that PP1 is the most likely protein phosphatase targeting pS269-AQP2 in vivo. Our results are in line with other studies that suggest a role for PP1 in regulation of AQP2 phosphorylation (Moeller et al, 2010;Zwang et al, 2009). A functional role for protein phosphatases in regulation of AQP2 has previously been suggested, although the effects of okadaic acid observed were attributed to a depolymerizing effect (disruption) on the actin cytoskeleton (Valenti et al, 2000).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the different running patterns of AQP2-E258K variants could also not be explained by differences in their masses [12,13]. Moreover, studies using circular dichroism showed that the secondary structure of non-phosphorylated peptides of the AQP2 C-terminus differs from the structure of peptides phosphorylated at S256 or S261 [29].…”
Section: The Nature Of the 30 Kda Aqp2-p262l Bandmentioning
confidence: 99%
“…Polyphosphorylation of AQP2 does not affect the relative unit water permeability of the channel (12), so it is unlikely to be involved in channel gating. Another hypothesis is that phosphorylation can influence AQP2 interactions with proteins involved in exocytosis or endocytosis (13), and several proteins have been identified that bind to AQP2, including Hsp70, Hsc70, clathrin, dynamin, AP2 (14), MAL (15), Spa-1 (16), lip 5 (17), annexin (18), Hsp50-5(BiP/ Grp78), and PP1 (13).…”
mentioning
confidence: 99%